ANALYSIS INFORMATION SYSTEMS FORCASH RECEIPTS FROM BUS TICKET SALES AT PT LURAGUNG JAYA LESTARI - Irawaty Irawaty (Asosiasi Dosen Muda Indonesia, 2023)
This study aims to analyze the accounting information system and cash receipt procedures from the sale of PO Luragung Jaya bus tickets and to evaluate the accounting information system and procedures applied to the PO company. Luragung Jaya is appropriate or not based on business aspects. The research method is qualitative, while the data analysis technique used is descriptive analysis of a qualitative approach. In this research data collection techniques include preliminary surveys, field studies with interviews and documentation. The results obtained from this study are the accounting information system and procedures in cash receipts are in accordance with business aspects, but not good enough. There is some documentation that is not yet appropriate and activities carried out without any special rules that are sustainable. The cash receipt system uses a computerized system but not all, there are some that are still manual causing non-uniformity in recording which can result in ineffectiveness in checking in the future.